2022
DOI: 10.3788/col202220.021404
|View full text |Cite
|
Sign up to set email alerts
|

Diode-pumped 13 W Yb:KGW femtosecond laser

Abstract: We report on a high-power diode-pumped Yb∶KGWO 4 2 (Yb:KGW) mode-locked laser with a semiconductor saturable absorber mirror (SESAM). For 32.7 W of incident pump power, we generate 261 fs pulses with the maximum average output power of up to 13.0 W and spectrum centered around 1039 nm at 68.4 MHz, corresponding to 190 nJ of single pulse energy and 0.72 MW of peak power. The optical-to-optical conversion efficiency is 39.8%, and the slope efficiency is 64.4%. The Yb:KGW laser exhibits a power stability better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This makes it an ideal choice for high-power diode-pumped solid-state lasers. Yb:KGW (Ytterbium-doped Potassium Gadolinium Tungstate) [5][6][7] offers a wide absorption bandwidth and emits in a broad range around 1020-1060 nm. It is frequently employed in femtosecond laser systems.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it an ideal choice for high-power diode-pumped solid-state lasers. Yb:KGW (Ytterbium-doped Potassium Gadolinium Tungstate) [5][6][7] offers a wide absorption bandwidth and emits in a broad range around 1020-1060 nm. It is frequently employed in femtosecond laser systems.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Most recently, Yang et al realized a Yb:KGW laser which the average output power up to 13 W with a 261 fs pulse duration. [4] Besides, multi-watts with sub-100 fs pulses have been reported by the combination of KLAS mode locking in recent years. In 2014, Zhao et al reported a Yb:KGW oscillator which could generated 78-fs pulses with a peak power of 0.65 MW and a telescope construction extended the cavity leading to single pulse energy obtained 50 nJ at a repetition rate of 36 MHz.…”
Section: Introductionmentioning
confidence: 99%